Recent Developments in Transannular Reactions - Reyes, Efraim; Prieto, Liher; Carrillo, Luisa; Uria, Uxue; Vicario, Jose L. (Synthesis, 2022)
Transannular reactions have shown a remarkable performance for the construction of polycyclic scaffolds from medium- or large-sized cyclic molecules in an unconventional manner. Recent examples of transannular reactions reported from 2011 have been reviewed, emphasizing the excellent performance of this approach when accessing the target compounds. This review also highlights how this methodology provides an alternative approach to other commonly used strategies for the construction of cyclic entities such as cyclization or cycloaddition reactions.1 Introduction2 Transannular Cycloadditions and Electrocyclizations3 Transannular Conjugate Additions4 Transannular 1,2-Addition to Ketones, Imines, Esters, and Amides5 Transannular Reactions via Electrophilic Activation of Olefins6 Transannular Ring-Opening of Epoxides7 Transannular Alkylations of Enolates and Related Species8 Miscellaneous Transannular Reactions9 Concluding Remarks
Keywords: transannular reaction; bicyclic compounds; cyclization; fused-ring systems; heterocycles; macrocycles; natural products; total synthesis